John Willy and Freddy McGee - Meade, Holly (New York : Marshall Cavendish, 1998)
Two guinea pigs escape from their safe but boring cage and have an adventure in the tunnels of the family's pool table.
Adult 580
Accelerated Reader AR
Keywords: Guinea pigs -- Juvenile fiction